Intratumoural immune cell landscape in germinoma reveals multipotent lineages and exhibits prognostic significance. (29th July 2019) - Takami, H.; Fukushima, S.; Aoki, K.; Satomi, K.; Narumi, K.; Hama, N.; Matsushita, Y.; Fukuoka, K.; Yamasaki, K.; Nakamura, T.; Mukasa, A.; Saito, N.; et al.
Abstract : Aims: Alterations in microenvironments are a hallmark of cancer, and these alterations in germinomas are of particular significance. Germinoma, the most common subtype of central nervous system germ cell tumours, often exhibits massive immune cell infiltration intermingled with tumour cells. The role of these immune cells in germinoma, however, remains unknown. Methods: We investigated the cellular constituents of immune microenvironments and their clinical impacts on prognosis in 100 germinoma cases. Results: Patients with germinomas lower in tumour cell content (i.e. higher immune cell infiltration) had a significantly longer progression‐free survival time than those with higher tumour cell contents ( P = 0.03). Transcriptome analyses and RNA in‐situ hybridization indicated that infiltrating immune cells comprised a wide variety of cell types, including lymphocytes and myelocyte‐lineage cells. High expression of CD4 was significantly associated with good prognosis, whereas elevated nitric oxide synthase 2 was associated with poor prognosis. PD1 (PDCD1) was expressed by immune cells present in most germinomas (93.8%), and PD‐L1 (CD274) expression was found in tumour cells in the majority of germinomas examined (73.5%). Conclusions: The collective data strongly suggest that infiltrating immune cells play an important role in predicting treatment response. Further investigation should lead to additional categorization of germinoma to safely reduce treatment intensity depending on tumour/immune cell balance and to develop possible future immunotherapies.